INSULATING CERAMIC INSERTS FOR CASTING PRODUCTS FROM ALUMINUM ALLOYS - A. T. Volochko (Литьë и металлургия, 2016)
The paper analyses production of reusable ceramic insulating inserts applied in permanent mold casting of aluminum alloys. It presents results of manufacturing of ceramic products from synthesized materials based on wollastonite, secondary grog, aluminum slag, etc. The paper demonstrates prospects of their applying.